The Frustrated Turn to Adversarial Procedure in Italy (Italian Criminal Procedure Code of 1988) - Giulio Illuminati (Washington University Global Studies Law Review, 2005)
After a challenging fight, the accusatorial-adversarial model has now been completely assimilated. The accusatorial “return,” however, is better in concept than in practice. An accusatorial system that does not work is not really accusatorial, especially, if it cannot grant exactly what it should, a better way of rendering justice. The present malfunctions in the system partially betray the process provided by and codified in the law. The first step towards ensuring a working accusatorial system is to seriously increase the resources available. The second step presents two possible options, either increase the forms of diversion, or drastically reduce the number of punishable crimes. A better solution would bring the two actions together.
Keywords: Adversary system; Criminal procedure; Italy. Code of Criminal Procedure; Italy